AWARENESS OF GHARAR IN SALE AND PURCHASE CONTRACTS AMONG KUALA NERUS SOCIETY - Dr. Najdah Abd Aziz,; Rafhanah Zakirah Rosley,; Rubiah Abu Bakar, (Journal of Islamic, Social, Economics and Development, 2022)
This study was conducted to identify the awareness of gharar in sale and purchasecontracts in the society of Kuala Nerus, Terengganu. Any uncertainties, doubts andshortcomings in the sale and purchase contracts are considered gharar. Using thequestionnaire as a research instrument, 120 sets were distributed through online forms amongrandomly selected Kuala Nerus society. The methodology of this study uses quantititavemethods. Descriptive analysis is used to analyse data in percentage, frequency, mean, modeand median. The result of the investigation found that the mean value shown in each variableis high level, the value of mean part B is 4.233 and part C is 4.3833 (high). At the end of thisstudy, the researcher suggested to conduct a more in-depth questionnaire on the understandingof gharar in the sale and purchase contracts. Researchers also suggest that other researchersdevelop their research aspects more widely, not only at the district level but also at thecomparative level by state.